VA Interprofessional Fellowship in Palliative Care: 15 Years of Training Excellence. Issue 2 (3rd July 2019) - Weller, Ryan; Healy, Jennifer; Hettler, Debbie L.; Howe, Judith L.; Smith, Heather M.; Steckart, M. Jillisa; Periyakoil, Vyjeyanthi S.
Abstract: Since 2002, the Department of Veterans Affairs (VA) has provided a unique training opportunity in palliative care at six VA medical centers. The VA Interprofessional Fellowship in Palliative Care has trained chaplains, nurses, pharmacists, physicians, psychologists, and social workers to provide clinical palliative care and to develop as leaders in the profession. This article describes the program's origin, mission, outcomes, and lessons learned.